Proportion of Depression Symptoms and Its Relationship with ARV Therapy: A Study at the VCT Clinic, Dr. Kariadi General Hospital - Sofro, Muchlis Achsan Udji; Raharja, Tommy; Haidati, Titis; Sari, Linda Kartika; Jusup, Innawati (UI Scholars Hub, 2022)
Introduction. Indonesia has the second largest HIV burden in Asia. The prevalence of depression in HIV/AIDS is 2-10 times higher than the general population, influenced by biological, environmental, psychological, and demographic factors. Data on the proportion of depression symptoms in HIV/AIDS patients and their relationship to biological factors are still limited, which needed for better treatment of HIV/AIDS. This study aimed to determine the prevalence of depression and its relationship to the biologic factors of ARV therapy (ART) in HIV/AIDS patients.Methods. Cross-sectional study was conducted among 142 HIV/AIDS patients undergoing ARV treatment at RSUP. Dr. Kariadi in January – March 2021. Demographic data, ART, ART type, side effects, ARV use duration, viral load, and CD4 cell count were obtained from medical records. The incidence of depression was assessed by the Beck Depression Inventory II (BDI-II).Results. The proportion of depression symptoms was 48.6%, consisting of mild depression (26.1%), moderate depression (17.6%), and severe depression (4.9%). Multivariate analysis resulted a significant relationship between the incidence of depression and biological factors, consisting of ART side effects, ART use duration, and CD4 cell count. Meanwhile, there was no significant relationship between the incidence of depression with the ART type and viral load. Conclusion. The proportion of depression symptoms in HIV patients undergoing ART is 48.6%. It is concluded that biological factors can affect the proportion of depression in patients with ART.